Regulatory Effects of Fecal Microbiota Transplantation on Inflammatory Cytokines in a DSS-Induced Colitis Mouse Model - Liu, Li; Xu, Yugui; Chen, Dongxu; Zhang, Junjie; Zhang, Ao; Bai, Xianguang (Trends in Immunotherapy, 2026)
Ulcerative colitis (UC) is an immune-mediated inflammatory disease characterized by excessive pro-inflammatory cytokine activity and impaired immune regulation. Fecal microbiota transplantation (FMT) has emerged as a microbiome-based immunotherapeutic approach, yet its effects on systemic immune responses in UC remain incompletely understood. This study examined the immunomodulatory impact of FMT in a dextran sulfate sodium (DSS)–induced murine model of colitis. Forty-five male C57BL/6 mice were randomly assigned to control, DSS model, and FMT-treated groups (n = 15 per group). Colitis was induced with 3% DSS for seven days, followed by a seven-day intragastric administration of fecal suspension in the FMT group. Clinical disease activity, gross colonic morphology, and serum cytokine levels were assessed. DSS exposure resulted in pronounced colitis, evidenced by weight loss, elevated disease activity index scores, and macroscopic colonic injury. FMT significantly alleviated disease severity, improved body weight recovery, reduced disease activity, and partially restored colon length. Furthermore, FMT markedly reduced circulating pro-inflammatory cytokines (TNF-α, IL-6, and IL-1β) while increasing the levels of anti-inflammatory cytokines IL-4 and IL-10 (all p < 0.01). These findings suggest that FMT attenuates DSS-induced colitis and promotes a systemic shift toward an anti-inflammatory immune profile. Study limitations include the absence of quantitative histopathological scoring and immune-cell phenotyping. Further mechanistic studies are warranted to elucidate the immunological pathways underlying FMT-mediated protection in UC.